Justification of the Coexistence of Formal and Informal Reciprocal Loans in Developing Countries - Zhao, Jianmei; Liu, Ruihan (Scientific Research, 2017)
This paper provides a new justification for the coexistence of formal and informal reciprocal loans in developing countries. We develop an investment model capable of comparing the financing costs of different financing alternatives. Notably, the reciprocal feature of interest-free loans from friends imposes an agnostic obligation on the borrower and generates implicit financing costs. The diverse financing outcomes hinge on the comparison of the explicit costs of formal loans and the implicit costs of reciprocal loans from friends.
Keywords: Coexistence; Reciprocal Loan; Financing Costs; China